POPULASI DAN INTENSITAS SERANGAN LARVA Spodoptera litura PADA TANAMAN KACANG TANAH Arachis hypogeae L. DI DESA KANONANG KECAMATAN KAWANGKOAN BARAT - Greyni P. Palit; Betsy A.N. Pinaria; Elisabeth R.M. Meray (COCOS, 2016)
ABSTRACTThe purpose of this research is to know the population and intensity attack of larvaS. litura to peanuts at Kanonang Kawangkoan Barat. Decided the research location, there aretwo planting locations of peanuts on 25x15 m2 wide. Then, every garden bed decided to fivesub plot monitoring that spread diagonally on size 3x3m.The result showed that the population of larva S. litura on peanuts at Kanonangvillage Kawangkoan Barat the highest was on 49 days old after planting at location A thatreached out 2,2 by clump and reached out 4,8 by clump of location B and the highestintensity attack was on 49 days old of plant at location A that reached out 17,61% and19,52% at location B.The more the plant had been growing old that more the population and intensityattack of a pest had been increasing, because the necessity of pest would be more increasing .Key words : Population, Attack Intensity, S. litura, Peanut